Real-World Safety Profile of Biologics Used in Rheumatology: A Six-Year Observational Pharmacovigilance Study in the Calabria Region - Agnese Gagliardi; Francesco Salvatore Iaquinta; Rosa Daniela Grembiale; Caterina De Sarro; Antonio Fabiano; Domenico Fraija; Caterina Palleria; Rossella Romeo; Adele Emanuela De Francesco; Maria Diana Naturale; Rita Citraro; Luca Gallelli; et al. (MDPI AG, 2022)
Background: The introduction of biological agents into the clinical armamentarium has modified the management of moderate-severe inflammatory arthritis (IA). However, these drugs can lead to serious adverse events (SAEs) and unpredictable adverse events (AEs) that are difficult to detect in pre-marketing clinical trials. This pharmacovigilance project aimed to study the AEs associated with biologics use in rheumatology. Methods: The current investigation is a multicenter, prospective, observational cohort study based on the Calabria Biologics Pharmacovigilance Program. Patients treated with one biologic agent from January 2016 to January 2022 were enrolled. Results: Overall, 729 (86.3%) of a total of 872 patients did not develop AEs or SAEs, whereas 143 (16.4%) patients experienced at least one AE, of which 16 (1.8%) had at least one SAE. The most common AEs were administration site conditions followed by gastrointestinal, nervous system and skin disorders. We reported a total of 173 switches and 156 swaps. Switches mainly occurred for inefficacy (136; 77.7%), whereas only 39 (22.3%) were due to the onset of an AE. Primary/secondary failure was the most frequent reason for swaps (124, 79%), while AEs onset led to 33 (21%) swaps. Conclusions: This study supports the validity of our program in monitoring and detecting AEs in the rheumatological area, confirming the positive beneficial/risk ratio of biologics.